STUDI PENDAHULUAN GEOLOGI GUA LAWA DI PURBALINGGA, JAWA TENGAH - Widagdo, Asmoro; Setijadi, Rachmad (Dinamika Rekayasa, 2007)
Lawa Cave in Purbalingga Regency is a special type of cave as it formed not at calcareous rocks like at theÂ usual cave. It is formed by lava flow processes. So, it is made of an igneous rock and it has an andesitÂ basaltic rock type. Lawa Cave formed due to lava flow of the volcanic eruption of the Old Slamet Volcano.Â The rocks composition of Lawa Cave consists of primary minerals that are plagioclase and volcanic glass andÂ some secondary mineral like calcite and ferri oxide which is fill the previous gas pores. Generally, rockÂ fractures in Lawa Cave is formed as primary joint when the lava flow was cooling down, tectonic joints isÂ found very limited. Lawa Caveâs direction is controlled by the flow direction of the melting lava. Itâs directionÂ indicate the paleomorphology of the volcano.